Cavity-assisted nondestructive laser cooling of atomic qubits - Griessner, A; Jaksch, D; Zoller, P (2004)
We analyse two configurations for laser cooling of neutral atoms whose internal states store qubits. The atoms are trapped in an optical lattice which is placed inside a cavity. We show that the coupling of the atoms to the damped cavity mode can provide a mechanism which leads to cooling of the motion without destroying the quantum information.